Access to Certified, Improved Rice Seed and Farmers' Income in Nigeria - Awotide, B.A.; Awoyemi, T.T.; Diagne, A. (Informa UK Limited, 2012)
Seed certification enhances seed quality and has the potential to increase rice (Oryza sativa L) yield and improve farmers' income. There is a dearth of information on factors that determine farmers' access to certified, improved rice seed and affect farmers' income in Nigeria. Hence, this study was conducted to fill this gap. The data were collected using a multistage random sampling technique. Osun, Niger, and Kano states were selected to represent upland, lowland, and irrigated rice growing systems, respectively. Five major rice-producing local government areas (LGAs) were selected from each state, followed by the selection of three villages from each LGA. In all, 600 rice farmers were selected on the basis of probability proportionate to the population of rice farmers in the villages. Data were collected using a structured questionnaire. Data were analyzed using descriptive statistics, the logistic regression model, and ordinary least square (OLS) regression. Contact with extension agents, access to media, age of household head, and years of formal education significantly increased the probability of access to certified, improved rice seed. Furthermore, agricultural expenditure (P 0.05), access to seed (P 0.01), household size (P 0.01), years of formal education (P 0.05), and income from other crops (P 0.01) had a significant positive effect on income from rice production. Increased access to the certified, improved rice seed, particularly through the formal seed-supply system, should lead to a significant improvement in the farmers' income and ultimately reduce the prevailing poverty among the farming households in Nigeria.